Dynamic analysis of foundation of Bir Hospital Trauma Centre, Kathmandu, Nepal - Adhikari, Ajay Raj; Adhikary, Prakash Chandra (Bulletin of the Department of Geology, 2008)
The rapid incrase in population of Kathmandu metropolitan city in last two decades has demanded the construction of multistoried buildings. As the height of building increases, variation in moments and force along the height of the structure becomes vulnerable and is more pronounced when the structure rests in soft fluvio-lacustrine sediments like in the Kathmandu Valley. Similarly, the amplitude of vibration causes bending of rebars which can damage the foundation and ultimately the building, if proper care is not taken during the design phase. Therefore, this paper aims in calculating the amplitude of vibration at natural frequency, seismic interial force and its change for the height of the Bir Hospital Trauma Centre, Kathmandu. The elastic parameter, modulus of elasticity needed for analysis was estimated from a graphical method. Shear modulus was calculated using empirical ralation. Density of strate was estimated in the laboratory and load of the structure was referred from Indian Standard of design loads. The maximum amplitude of vibration calculated was 12 mm at 19.3 Hz whereas it was 1.5 mm at the natural frequency for all portions avoiding coupling effect. The variation in seismic horizontal force and moment was largest at the height of 9-15 m showing the possibility of failure at such height at the time of earthquake. doi: 10.3126/bdg.v10i0.1420 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 55-62